2021
DOI: 10.1002/tox.23362
|View full text |Cite
|
Sign up to set email alerts
|

Corynoline protects lipopolysaccharide‐induced mastitis through regulating AKT/GSK3β/Nrf2 signaling pathway

Abstract: Inflammation has been known to be involved in the pathogenesis of mastitis. And anti-inflammatory agent is proposed to be a possible efficient therapeutic strategy for mastitis. Corynoline, a bioactive compound extracted from Corydalis bungeana Turcz., has been reported to have anti-inflammatory effect. However, whether corynoline has protective effect against mastitis remains unclear. The aim of this study was to evaluate the protective effect of corynoline on LPS-induced mastitis in mice.Inflammatory cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, we demonstrated the decreased Nrf2 expression by ML385, followed by the significantly weakened efficacy of Corynoline. Wu et al proposed that Corynoline activated the Nrf2 pathway by promoting the phosphorylation of AKT and GSK3β (Wu et al, 2021 ). Liu et al reported that Corynoline exerted its effects by manipulating the Nrf2 pathway and suppressing NF‐kB activation (Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we demonstrated the decreased Nrf2 expression by ML385, followed by the significantly weakened efficacy of Corynoline. Wu et al proposed that Corynoline activated the Nrf2 pathway by promoting the phosphorylation of AKT and GSK3β (Wu et al, 2021 ). Liu et al reported that Corynoline exerted its effects by manipulating the Nrf2 pathway and suppressing NF‐kB activation (Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al ( 2022 ) demonstrate this component to alleviate osteoarthritis via the Nrf2/NF‐kB pathway. In addition, Wu et al reported that it could protect lipopolysaccharide‐induced mastitis by manipulating the Nrf2 signaling pathway (Wu et al, 2021 ). However, the specific mechanism that Corynoline ameliorates oxidative stress‐induced damage remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Following the exposure of lung tissues to foreign substances like LPS (endotoxins), the immune system reacts with the proinflammatory cytokines. Cytokines are low molecular weight soluble glycoproteins that are secreted by various cells and tissues 58 . This activates an immune response, causing inflammation as a way to eliminate the foreign substances and protect the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are low molecular weight soluble glycoproteins that are secreted by various cells and tissues. 58 This activates an immune response, causing inflammation as a way to eliminate the foreign substances and protect the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The doses of corynoline used in this study were based on previous studies. [14,15] The mice of corynoline (60mg/kg)+EX-527 (10 mg/kg) + ZEA group were given corynoline (60 mg/kg) and EX-527 (10 mg/kg) by intraperitoneal injection for 5 days and then administrated ZEA. The mice were ultimately nesthetized and killed for subsequent experiments.…”
Section: Animals and Treatmentmentioning
confidence: 99%